Confinamento de líquidos em nanoescala - Blanco, Asdrubal Lozada (Universidade Federal de São Carlos, 2012)
The effects on the reduction of space on the structural properties of two liquids and a mixture thereof were analyzed with a definition of nanoscale confinement, based on carbon nanotubes. The methodology involves the use of the Monte Carlo Method at isobaric-isothermal assembly, , and Radial Distribution Functions for structural analysis. The results showed that in confinement conditions presents formation and distortion of structural patterns in the correlation functions for the studied liquids, water and methanol. The variations in these functions are presented as dependent on the description of the nanotubes.
Keywords: Físico-química; Confinamento de fluídos; Método de Monte Carlo; Distribuição radial; Líquidos; Confinement; Liquids; Monte Carlo; Radial Distribution; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA